2018
DOI: 10.1093/jscr/rjy314
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic necrosis of small bowel following small bowel obstruction as a late complication of sex reassignment surgery—a gap in transgender care

Abstract: For decades, Thailand has been at the forefront of sex reassignment surgeries. The neovagina created by recto-sigmoid vaginoplasty is much more complex procedure when compared with penile skin version technique, but yielded more satisfactory functional outcomes. We reported an unusual case of life-threatening small bowel obstruction following previously successful recto-sigmoid vaginoplasty in a transgender woman. Transgender individuals have unique healthcare needs. However, various gaps still exist to provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Data on complications associated with intestinal vaginoplasty specifically are sparse. There are published case reports describing intestinal necrosis postoperatively with significant sequelae to patients, 17,18 but in general, there are significant knowledge gaps about overall outcomes in the transgender patient population. In a series of 24 patients who underwent intestinal vaginoplasty as a secondary procedure, van der Sluis et al reported that 1 in 8 of the intestinal neovaginas were removed for postoperative complications and almost 80% underwent at least one genital reoperation such introitoplasty.…”
Section: Intestinal Vaginoplastymentioning
confidence: 99%
“…Data on complications associated with intestinal vaginoplasty specifically are sparse. There are published case reports describing intestinal necrosis postoperatively with significant sequelae to patients, 17,18 but in general, there are significant knowledge gaps about overall outcomes in the transgender patient population. In a series of 24 patients who underwent intestinal vaginoplasty as a secondary procedure, van der Sluis et al reported that 1 in 8 of the intestinal neovaginas were removed for postoperative complications and almost 80% underwent at least one genital reoperation such introitoplasty.…”
Section: Intestinal Vaginoplastymentioning
confidence: 99%